Geometric characteristics and optical performance of ACPCs for integration with roofing structure of buildings - Xu, Ruihua; Tang, Runsheng (Energy reports, 2021)
Stationary compound parabolic concentrators (CPC) are usually oriented in the east–west direction and tilted towards the equator for efficient radiation concentration. However, the slope (β) of roofing structure integrated with CPCs may be not equal to site latitude (λ) in buildings, thus asymmetric CPCs (ACPC) should be used. In this work, geometric characteristics and optical performance of ACPCs integrated onto roofs of buildings are investigated. To perform this work, a mathematical procedure, in which three and four reflections within ACPCs with flat-plate (ACPC-1) and tubular (ACPC-2) absorbers are respectively considered, is suggested and validated by ray-tracing analysis. Analysis shows that the geometric concentration of ACPCs on a south-facing roof tilted at an angle (α=λ-β) relative to the site latitude is not only dependent on angular extent (2θa) of solar rays required for acceptance on the cross-section of linear ACPCs, but also dependent on the geometry of absorbers and α. Calculation results indicate that given θa, the geometric concentration ratio (Ct) of horizontally truncated ACPC-1 decreases with an increase of α but that of ACPC-2 increases. Compared to similar symmetric CPC, an appropriately designed ACPC not only reduce the use of reflector materials but also increase the annual collectible radiation (Sa). It is found that as compared to similar symmetric CPC, for ACPC-1 with θa=35.5° and ρ=0.9, 7° and 10° of |a| result in reduction of Sa less than 1%, and 2%, respectively; whereas for ACPC-2, 10° and 15° of |a| result in reduction of Sa less than 1%, and 2%, respectively.